Readiness of Public TVET for the Fourth Industrial Revolution: The Case of South Africa - Denhere, Varaidzo; Moloi, Tankiso (INVOTEC, 2021)
This study aimed at determining the readiness of South African Public Technical and Vocational Education and Training (TVET) Colleges to operate in the 4IR. An assessment of the indicators deemed to prove readiness by the researchers of this study basing on literature was conducted through virtually interviewing public TVET College Principals, Deputy Principals Academic, Human Resources Managers and ICT Managers. A purposive sample of 26 from a population of 50 public TVET colleges proportionally representing the 9 provinces of South Africa was identified. The interviews were video recorded and later transcribed. From the findings it was concluded that most of the public TVETs realised the importance of readiness for 4IR as they got a push from Covid-19 and started or intensified preparing but were not completely ready due to lack of or inadequate teaching and learning technologies, training for teaching staff on the use of available technology; poor connectivity; lack of computing equipment; lack of ICT infrastructure; lack of ICT Strategies; and above all lack of policy directive. The findings could be used by the South African government to inform policy formulation and supporting higher education and training as a response to demands of 4IR to promote readiness by public TVETs to operate in the era characterised by intense technological changes.